Receipt of recommended surveillance with imaging in elderly survivors of early stage non-small cell lung cancer. (November 2018) - Malhotra, Jyoti; Rotter, David; Jabbour, Salma K.; Aisner, Joseph; Lin, Yong; Manne, Sharon; Demissie, Kitaw
Highlights: Many lung cancer survivors do not receive recommended surveillance imaging. Age, race and access to care are barriers to receiving recommended surveillance. Receiving recommended imaging is associated with improved long-term survival. Abstract: Purpose: Early-stage lung cancer survivorsremain at high risk for recurrence or second cancers. We measured the rates and determinants of regular surveillance imaging in early-stage non-small cell lung cancer (NSCLC) survivors. Methods: Patients (diagnosed 2001–2011) with resected stage I and II NSCLC were identified from the Surveillance Epidemiology and End Results (SEER)-Medicare linked database. Patients were censored at recurrence/second cancer diagnosis, loss to follow-up or death. Receipt of a scan during the surveillance periods of 7–18, 19–30, 31–42 and 43–60 months from date of surgery was assessed. Results: Of 10, 680 survivors assessed during the 18-month surveillance period, 71% received imaging in first 18 months. Only 56% and 43% continued to receive regular imaging by 30-month and 60-month of follow-up, respectively. Survivors were less likely to receive imaging if they were older, black, unmarried, received no adjuvant therapy, had stage I disease (vs. stage II) or were diagnosed before 2006. In adjusted analysis, survivors who received recommended imaging up to 18 months from surgery experienced better survival compared to survivors who did not (HR 0.92; 95% CI 0.85–0.99). Survival benefit was also observed in survivors who underwent regular imaging up to 5 years from surgery (HR 0.68; 95% CI 0.60–0.78). Conclusions: More than half the lung cancer survivors received less than the recommended long-term surveillance imaging. Long-term adherence to surveillance is associated with improved survival. Our study provides evidence to support the current clinical guidelines for surveillance for lung cancer survivors that are primarily consensus-based at present.